2008
DOI: 10.1002/hep.22387
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for adiponectin in regulating the immune responses in chronic hepatitis C virus infection†‡

Abstract: Adipose tissue releases pro-inflammatory and anti-inflammatory mediators, including adiponectin, which elicit a broad range of metabolic and immunological effects. The study aim was to determine in subjects infected with chronic hepatitis C virus (HCV) the effects of total adiponectin and its high-molecular-weight (HMW) and low-molecular-weight isoforms on HCV-specific immune responses. Serum levels of total adiponectin and its isoforms were determined by immunoassay. The ex vivo effect of adiponectin on the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 47 publications
6
48
0
1
Order By: Relevance
“…Quantitative real-time PCR detected both AdipoR1 and AdipoR2 mRNA in dermal gd-T cells, although AdipoR2 protein expression was below the detection limit by western blot analysis. This result is consistent with the past reports demonstrating discrepancy between mRNA and protein levels of AdipoR2 in leukocytes 41,42 . Control experiments have revealed that AdipoR1 and AdipoR2 mRNA levels are reduced by 465% as evaluated by real-time reverse transcription-PCR analysis (Fig.…”
Section: Resultssupporting
confidence: 94%
“…Quantitative real-time PCR detected both AdipoR1 and AdipoR2 mRNA in dermal gd-T cells, although AdipoR2 protein expression was below the detection limit by western blot analysis. This result is consistent with the past reports demonstrating discrepancy between mRNA and protein levels of AdipoR2 in leukocytes 41,42 . Control experiments have revealed that AdipoR1 and AdipoR2 mRNA levels are reduced by 465% as evaluated by real-time reverse transcription-PCR analysis (Fig.…”
Section: Resultssupporting
confidence: 94%
“…Examination of the expression of the adiponectin receptors, AdipoR1 and AdipoR2, in these cells concurred with a previous report (37) showing that CD4 ϩ T cells express AdipoR1 preferentially (data not shown). To investigate the effects of adiponectin on purified CD4 ϩ T cells, we subjected these human cells to polyclonal stimulation in the presence or absence of adiponectin and examined the expression of IFN-␥ and IL-4, signature cytokines of the T H 1 and T H 2 lineages, respectively, and of the broad inflammatory mediator IL-6.…”
Section: Adiponectin Promotes T H 1 Differentiation Of Isolated Cd4supporting
confidence: 91%
“…In contrast, adiponectin limits both T cell proliferation and apoptosis when added to human PBMCs together with a polyclonal T cell activator (36). Recent studies addressing the role of adiponectin on the expansion of antigen-specific T cell populations from human PBMCs have also yielded discordant results as follows: adiponectin reduced the number of influenza-specific T cells producing IFN-␥ and TNF-␣ (36) but increased IFN-␥ production by hepatitis C virus-specific T cells (37). These results indicate that the action of adiponectin on T cell differentiation and function varies among species and that the experimental conditions used in vitro (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Palmer et al (145) high concentrations of total and high-molecular weight adiponectin were related to the presence of a cellular immune response against HCV, suggesting a pivotal role for adiponectin in the regulation of immunity in CHC. The study by Latif et al (146) showed that serum adiponectin levels inversely correlate not only with the grade of steatosis and histological activity index, but also with the stage of fibrosis (146).…”
Section: O V E M B E R -D E C E M B E R 2 0 1 1 L E P T I N a D I Pmentioning
confidence: 97%